Geopolytic enemies and post-colonialism in the context of romance Neighbours, by Lília Momplé - Gonçalves Moraes, Claudia Letícia (2020)
This essay proposes a critical analysis of the novel Neighbors (1995), by Mozambican writer Lília Momplé, proposing a reading that analyzes the neighborhoods of enmity between Mozambique and South Africa in the post-independence period that present themselves as the central motto of the narrative and mobilization of your characters. Thus, it is intended to observe how the animosity between the two countries draws a picture of social instability in post-independence Mozambique in the 1990s, shaping a series of violence that constitute the frightening Mozambican daily life, as well as other geopolitical and social conflicts that settled in post-colonialism. For theoretical analysis of the highlighted aspects, authors such as Achille Mbembe (2017, 2018), Jéssica Falconi (2015, 2012), Anselmo Peres Alós (2011) and Ana Mafalda Leite (2004) will be used, among other authors to assist us in the discussion about the concept of post-colonialism and in the criticism of the violent panel of geopolitical neighborhoods based on the policies of enmity between border countries involved in intricate dynamics of movement of subjects that culminate in fierce conflicts in post-colonial contexts.